(untitled) (Acta Scientiarum. Agronomy, 2017)
Nationally known in Brazil, the jabuticabeira or jabuticaba tree produces fruits of wide commercial acceptance. However, little use of jabuticaba in commercial orchards and large genetic erosion of jabuticaba caused by human activities in its habitats have been historically observed. Thus, the goal of this study was to characterize fruits of the jabuticaba tree (Plinia cauliflora) in a forest fragment maintained in southwestern Paraná State in an attempt to identify trees with superior fruits for future selection as cultivars or male genitors. To this end, 15 variables linked to sensory and biochemical characteristics of harvested fruits were analysed during two years of production. Twenty percent of the genotypes that showed the highest frequency of superiority in the evaluated characteristics were preselected for analysis. The quality of the analysed fruits indicated their potential for use. Thus, this work resulted in the preselection of jabuticaba genotypes 7, 42, 43, 47, 54, 91, 97, 104, 105, 118, 134, 153, 154, 157, 163, 169, 177, 186, 212, J7-01, and J7-02, with 16 and 194 the only genotypes that had already been selected for superior characteristics during both growing cycles.